Pola Interaksi Parasitoid Larva Diadegma semiclausum Hellen (Hymenoptera: Ichneumonidae) dengan Plutella xylostella L. (Lepidoptera: Plutellidae) pada Tanaman Kubis yang Diperlakukan dengan insektisida Berbahan Aktif Emamectin Benzoat 5,7% - I KADEK WISMA YUDHA; I WAYAN SUSILA; I MADE MEGA ADNYANA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2017)
Interaction Pattern of Larvae Parasitoid Diadegma semiclausum Hellen (Hymenoptera: Ichneumonidae) by Plutella xylostella L. (Lepidoptera: Plutellidae) on Cabbage Treated by Insecticide Emamectin Benzoate 5.7% The research Interaction Pattern of Larvae Parasitoid Diadegma semiclausum Hellen (Hymenoptera: Ichneumonidae) withPlutella xylostella L. (Lepidoptera: Plutellidae) on Cabbage Treated by Insecticide Emamectin Benzoate 5.7% .The aims of this study is to know the interaction pattern, population and parasitization level of D. semiclausum which was treated by insecticide with the active ingredient is emamectin benzoat 5.7%. The design of this study is randomized block design (RBD)usingfivelevel of treatments (control, 0,25; 0,50; 0,75 and 1,00) and five replications. The result of this research showed the interaction pattern of parasitoid was not influenced by the treatment of insecticide. The population of parasitoid D. semicalusum was not significant difference between the treatment. Thepopulation of parasitoid in Buahan village and Kerta village were 5,40 and 4,80 respectively. The parasitizationrate in Buahan village and Kerta Village waere not signification effect between the treatment. The population of D. semiclausum in Kerta and Buahan Village